The effect of tranilast on MMP-2 and MMP-9 mRNA levels in normal and keloid fibroblasts - Antończak, Paweł P; Adamczyk, Katarzyna; Garncarczyk, Agnieszka; Jurzak, Magdalena (Przegląd dermatologiczny, 2018)
Introduction Tranilast (N-(3’,4’-demethoxycinnamoyl)-anthranilic acid) is an anti-allergic drug. Its mechanism of action is based on the inhibition of antigen-induced release of chemical mediators from mast cells and basophils. It exerts antifibroproliferative activity as well. These properties of tranilast are used in the treatment of hypertrophic scars and keloids. Keloid fibroblasts exhibit overproduction of collagen type I and decreased degradation of extracellular matrix in comparison with normal fibroblasts. Matrix metalloproteinases play the key role in extracellular matrix turnover. Objective Quantitatively evaluate MMP-2 (gelatinase A) and MMP-9 (gelatinase B) gene expression in normal human skin fibroblasts and fibroblasts derived from keloids exposed to tranilast in vitro. Material and methods The experimental material constituted two cell lines: normal human dermal fibroblasts (NHDF) and keloid fibroblasts (KEL FIB). In the first stage of the study, the influence of tranilast on cell viability was estimated. The second stage of the study involved the quantitative evaluation of MMP-2 and MMP-9 gene expression in RNA extracts from fibroblasts treated with tranilast. Real-time QRT-PCR was used to validate the transcription level of MMP-2 and MMP-9 genes in NHDF and KEL FIB cells after tranilast treatment. Results Tranilast reduces the viability of the fibroblasts of both cell lines in 300 μM. The performed analysis indicates a stimulating effect of tranilast at 3 μM and 30 μM on the expression of MMP-2 in normal fibroblasts and at 3 μM on keloid fibroblasts. Tranilast did not influence the expression of MMP-9 mRNA, either in normal fibroblasts or in keloid fibroblasts. Conclusions Tranislast reduces the viability of normal and keloid fibroblast and modulated expression of MMP-2. Hovewer its activity is dose dependent. It is necessary to continue the study to evaluate full antiproliferative activity of tranilast.